As lutas sociais e a crise do socialismo no contexto do golpe de 2016 - Keller, Rene José (2019)
The title of this thesis could be "Marxism without mise en scène", because the concern that guides the study is not to promote an intransigent defense of the validity of the theoretical categories of this tradition. What I aim to do is examine them in the light of the recent political events, from June 2013, through the 2016 coup, to the election of Jair Bolsonaro in 2018, in order to measure theoretical compatibility with the actual course of social struggles at the beginning of the 21st century. In order to achieve the goals, it is necessary to reflect what represents, in the comparison with reality and its contradictions, the class struggle, the class consciousness, the role of the working class, the action of ideology, alienation/estrangement, the topical infra and superstructure, and the idea of socialism. A qualitative empirical research was carried out with people who participated in demonstrations over the years 2015-2016, opposing and supportive of impeachment, although I defend that it was an institutional coup. Based on the perspective of critical thinking, on the Marxist side, the guiding method of work is the dialectic in the materialist foundation. The fateful thesis defended is that, considering the historical outdatedness of socialism, due to the ecstatic use of Marxist theory without the concrete material base on which it must necessarily be thought, it is necessary to promote changes in its course, integrating the most diverse forms of oppression. The contribution of the study is to provide an analysis of the repercussions of the recent political events - June 2013, the coup of 2016 and the rise of neoliberal neofascism - to the socialist perspective, seeking to point out, starting from the historical and social conjuncture, reinvigorating this worldview.